Adjuvant Treatment for Ampullary Cancer - Kim, Richard; Chabot, John; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Ampullary cancer is an uncommon tumor and tends to have a better prognosis than pancreatic cancer. However, one half of patients will die from recurrent disease suggesting the need for effective adjuvant therapy. Currently, there is lack of randomized trials to guide the use of adjuvant therapy in ampullary cancer. At the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting, the largest trial (Abstract #4006) evaluating adjuvant treatment of ampullary cancer was presented. Image: H. Lee Moffitt Cancer Center. Tampa, FL, USA.